Information Governance and Transparency Information: Two Sides of the Same Coin? - Indah Novita Sari; Lillyana Mulya; Irfan Rizky Darajat (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: Information governance plays a central role in ensuring transparency, accountability, and compliance in public institutions. In the context of public administration, particularly in Indonesia, the implementation of information governance remains inconsistent, leading to issues such as information disputes and limited access to public data. The Freedom of Information (FOI) Act was established to promote openness; however, its success depends significantly on the maturity level of information governance in public institutions.